Taurine-conjugated bile acids are the predominant form in hens and have potential impact on lipid metabolism in the liver - Wen-Yuan Yang; Pei-En Chang; Yi-Ting Chen; Pei-Xin Liao; Yuan-Yu Lin (Italian Journal of Animal Science, 2023)
In mammals, bile acids composition varies with species, age, physiological conditions. However, the role of bile acids in the laying cycle of hens and their impact on lipid metabolism in chicken liver is not well understood. This study aimed to elucidate the role of bile acids in hen laying cycles, investigating their distribution across ages and assessing the impact of taurine-conjugated lithocholic acid (TLCA) on oleic acid-induced fatty liver cells in chickens. Results revealed an age-related increase in total bile acid concentration in hens blood, with taurine-conjugated bile acids prevailing. Among specific bile acids analysed, taurodeoxycholic acid (TDCA) decreased with age, while taurochenodeoxycholic acid (TCDCA) increased (n = 8). TLCA concentration also decreased gradually, while lycocholic acid (GCA) was elevated in 16-week-old hens (n = 8). Primary bile acids, cholic acid (CA), and chenodeoxycholic acid (CDCA) were higher at 16 weeks compared to egg production commencement (22 weeks) and 34 weeks (n = 8). Moreover, 5ß-Cholenic acid-7a-ol-3-one concentration was elevated in 74-week-old hens post-laying (n = 8). Investigating TLCA's impact on chicken liver lipid metabolism, TLCA significantly reduced lipid droplet accumulation, especially at 20 μM, while upregulating TLCA concentrations correlated with decreased SREBP1 protein expression responsible for triglyceride synthesis. In conclusion, taurine-conjugated bile acids potentially regulate lipid metabolism in hens, offering avenues for enhancing hens health and production through further mechanistic exploration and their potential integration into hens feed.